Enhancing cooperation during pediatric ultrasound: Oral midazolam versus conventional techniques - Rachna Chaurasia; Anshul Jain; Narendra Singh Sengar; Shivali Pandey (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: Ultrasound is a safe and non-invasive method for detecting numerous pathologies. Pediatric patients are often uncooperative which leads to decreased quality and increased time of scan. We compared the conventional means alone and combination of oral midazolam for the above cited purpose. Material and Methods: This double blind prospective study (CTRI/2016/06/007030) was conducted after obtaining due approval from institutional ethical committee. One hundred Children aged 2-6 years belonging to ASA class 1 or 2, posted for high resolution ultrasonography of abdomen were included in the study. They were randomised to receive midazolam 0.3 mg/kg mixed in 20 mL of apple juice (Group I) or 20 mL of apple juice alone (Group II) 20 minutes prior to the procedure. The parameters assessed were level of cooperation, sonologist's satisfaction, total scan time, heart rate and SpO2. Results: Out of 100 patients, 44 patients of group I and 42 of group II were analysed. The cooperation score was significantly higher in Group I (35%) than Group II (19%). Likert scale revealed very satisfied and satisfied rating in 61.3% (Group I) and 21.4% (Group II). The time taken by sonologist and number of attempts were significantly less in Group I than Group II. There was no difference in discharge time between the groups. There was no reportable adverse event in either group. Conclusion: Oral midazolam is a safe and effective agent to aid routine abdominal ultrasonography in pediatric patients.